Earthquake Induced Displacement and living arrangements in Nepal (Voice of Teacher, 2021)
The article is based on the issues of IDPs in Nepal. Introduction of IDPs is the main focus of the article whereas it deals with the methodology and show the status of Nepal in the world. It is the quantitative descriptive types of study. The objective of the study is to identify the status of living arrangements, shelter sources of water and toilet facility of IDPs. The IDPs have the very poor situation of living arrangements. The government must take initiatives to protect the IDPs. And further research must be conducted in the issues of IDPs.